Ila Mamati's Prayer Method of Memorizing the Al-Qur’an at High School at the Tahfidzul Qur'an Islamic Boarding School, Nurul Istiqalal Wonosari Klaten - Luthfi Badrus Tsani; Fauzi Muharom (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Prayer ila mamati is a phrase taken from Arabic. Sholati means my prayer, ila means until, while mamati means my death. So